Exploring student experiences within the alternative high school context - Morrissette, Patrick John (Canadian Journal of Education/Revue canadienne de l’éducation, 2011)
This paper describes a phenomenological study that explored the experiences of off-campus high school graduates. Twenty students participated in individual, tape-recorded interviews, during which they described their experiences, yielding written protocols that were thematically analyzed. Results from this study revealed five predominant themes that included the following: (a) ambiance (b) sense of belonging, (c) pedagogical skill, (d) program flexibility, (e) self-awareness. Findings and implications for educators, administrators, and future research are included.